ANTHROPOMETRIC PROFILE OF CHILDREN WITH CYANOTIC AND NONCYANOTIC CONGENITAL HEART DISEASE - Mahrus Rahman; I Ketut Alit Utamayasa; Taufiq Hidayat; Roedi Irawan; Rina Elizabeth (Media Gizi Indonesia, 2020)
Impaired nutritional status is a frequent complication of congenital heart disease (CHD). Non cyanotic congenital heart disease (NC-CHD) have problem with lung overfl ow and heart failure. Consequences of Cyanotic congenital heart disease (C-CHD) are decrease pulmonary blood fl ow and prolong hypoxia. These conditions can have eff ect on nutritional status and outcome of surgery. This study aimed to compare anthropometric profi les of children with C-CHD and NC-CHD. Cross-sectional study conducted in 66 children, age 3 months until 5 years old who met inclusion criteria in Pediatric Cardiology Outpatient Unit Dr. Soetomo Hospital Surabaya in November 2012. A total of 66 children, consisted of 26 children with C-CHD and 40 children NC-CHD included in study. We measure weight, length/height, head circumference, upper arm circumference, and skin fold thickness. We used Chi Square test for statistical analysis with Confi dence Interval 95%. Mean age of both groups was 27.82 ± 16.63 months. Majority of NC-CHD was Ventricular Septal Defect (28.6%) and C-CHD was Tetralogy of Fallot (21.4%). There were no signifi cant diff erence from weight for age, length for age weight for length, head circumference for age, mid upper arm circumference for age, mid upper arm circumference for age, and skin fold thickness for age between children with C-CHD and NC-CHD (p= 0.80; 0.98;0.54 0.29; 0.80; 0.53 respectively). There were no diff erence in anthropometric profi les among children with cyanotic congenital heart disease and non-cyanotic congenital heart disease in this study.